Initiatives for the Convergence of Supervision Regulations and Systems of Globally Operating Insurance Companies - Kurek, Robert (Studia Oeconomica Posnaniensia, 2013)
This study presents solutions and initiatives, undertaken by different international institutions and associations, aimed at the convergence of supervision regulations and systems in companies operating globally. Through analysing and evaluating tchem it was possible to identify the benefits which such convergence could bring. Since it is difficult to establish "common regulations" at a global level, the activities and initiatives undertaken can ensure only a fragmentary convergence of supervision systems. However, because even partial convergence provides a higher efficiency of supervisory procedures, facilitates the operations of insurance institutions and, on the macro scale, helps minimise systemic threats, it seems evident that any attempts to standardize regulations and supervision should be regarded as appropriate and highly desirable.